Perancangan Sistem Informasi Penjualan Berbasis Web Lincah Variasi Store - Bagus Saputro, Susanto Hertio; Amroni, Amroni; Gusriyanti, Dwi Ayu (LPPM Universitas Dinamika Bangsa, 2024)
Abstract− The influence of technology on everyday human life at this time has a very large impact. One of the inFormation technology that is being discussed at this time is the internet, which has become a necessity for the community and is widely used by companies or shops in marketing and data processing. Lincah Variation Store is a business venture engaged in the sale of car accessories and equipment. Over time, consumer demand for car accessories and equipment has also increased, but currently the system at the Lincah Variations Store is still conventional. This often causes errors in processing transaction data. Therefore we need a system that can increase the effectiveness and efficiency of work. In this study, the author tries to design a web-based sales inFormation system. Where the author develops the system using the waterfall method and UML (Unified Modeling Language) in the modeling. This system provides a new solution for processing sales transaction data at the Lincah Variations Store. Keywords: System, Information, Web, Lincah Variasi Store